2021
DOI: 10.1016/j.heliyon.2021.e07358
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of the hydrological response to land cover changes in the sub-basin of the Chicú river, Colombia

Abstract: Spatio-temporal analysis of the hydrological response to land cover changes in the sub-basin of the Chicú river, Colombia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Population increase is a variable that leads to substantial changes in the Spatio-temporal variation of land use and contributes to the loss of water bodies and green areas (Barreto-Martin et al 2021). Additionally, anthropogenic heat release can be related to the population and its per capita energy use; the pattern of energy use impacts the heat generated by anthropogenic sources.…”
Section: Socio-economic Factorsmentioning
confidence: 99%
“…Population increase is a variable that leads to substantial changes in the Spatio-temporal variation of land use and contributes to the loss of water bodies and green areas (Barreto-Martin et al 2021). Additionally, anthropogenic heat release can be related to the population and its per capita energy use; the pattern of energy use impacts the heat generated by anthropogenic sources.…”
Section: Socio-economic Factorsmentioning
confidence: 99%
“…In Colombia most of the hydrological modeling efforts have focused on the Magdalena-Cauca macro basin, which drains an area 254,0000 km 2 of the Andean region and it is considered the most important basin in the country. Some applications of hydrology modeling in Colombia includes management practices in agriculture using SWAT model (Uribe et al 2018), land cover and land use changes impact in hydrology response using SWAT (Villamizar et al 2019, Barreto-Martin et al 2021, the impact of climate change and deforestation in Magdalena-Cauca using WaterWorld model (Rodríguez et al 2020), flash flood event in an ungauged basin using TETIS model (Velásquez et al 2020), the impact of satellite rainfall products on streamflow simulations using Elementary Watershed (REW) and HBV-96 models (Elgamal et al 2017, López et al 2018, the impact of hydropower development on wetlands using WEAP model (Angarita et al 2018) and the groundwater recharge under different rainfall scenarios using TETIS model (Jimenez et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scholars have conducted studies on the impact of LUCC on streamflow and hydrological factors using the SWAT model. For example, studies showed that vegetation degradation such as agricultural land, grassland, and forest, as well as the increase of urban land, would all lead to a significant increase in streamflow or surface runoff [17][18][19][20]. The conversion of grassland to cultivated land resulted in an increase of flow, and the transformation from forest land to cultivated land, grassland to cultivated land, and grassland to forest land all weakened the regulation and storage capacity and easily changed the water yield of the sub-basin [21].…”
Section: Introductionmentioning
confidence: 99%